Being a boy again : autobiography and the American boy book - Jacobson, Marcia Ann (University of Alabama Press, 1994)
Marcia Jacobson's Being a Boy Again identifies a literary genre that flourished between the Civil War and World War I - the American boy book. Jacobson distinguishes the boy book tradition from the didactic story for boys and the developmental autobiography of childhood, describing it as an autobiographical form that concentrates on boyhood alone. She discusses what gave rise to the boy book, what forms it took, what problems it addressed, and finally, why it disappeared.